Chronic heart failure risk factors in patients with chronic kidney pathology - O. E. Ilyicheva (Кардиоваскулярная терапия и профилактика, 2008)
Aim. To investigate risk factors (RF) of chronic heart failure (CHF) in patients with various stages of chronic kidney pathology (CKP).Material and methods. All participants (n=154) were divided into three groups: Group I 52 patients with mild CKP, Group II 52 individuals with moderate CKP, and Group III 46 persons with severe CKP. In all participants, lipid profile, lipid peroxidation and antioxidant system parameters, left ventricular (LV) structure and function (by echocardiography) were examined.Results. According to multivariate regression analysis, in Group I systolic and diastolic blood pressure (SBP, DBP) independently affected LV diastolic function (DF). In group II, hemoglobin (Hb) level was an independent predictor of some LV DF parameters. In Group III, Hb level predicted some LV DF parameters, albumin predicted peak early diastolic filling (p=0,01), glomerular filtration rate predicted peak systole6diastolic filling (p=0,001), and SBP predicted LV ejection fraction (p=0,001).Conclusion. In severe CKP, “non-traditional” CHF RF become more important in myocardial dysfunction progression.